Electrospinning of recombinant human-like collagen-reinforced PCL nanofibrous membranes using benign solvents for periodontal regeneration - Ren, Minyi; Li, Meng; Boccaccini, Aldo R.; Xu, Yan; Li, Lu; Zheng, Kai (International Journal of Biological Macromolecules, 2025)
Periodontal tissue defects are a leading cause of tooth loss in adults. Guided tissue regeneration (GTR) has emerged as an effective clinical approach for promoting periodontal regeneration. In this study, we employed a green electrospinning technology to combine recombinant human-like collagen (RHC) with polycaprolactone (PCL) to fabricate RHC/PCL membranes for periodontal regeneration. Our results showed that incorporating RHC into PCL up to 40 wt% did not significantly affect the nanofibrous structure of the PCL membranes. When the RHC concentration exceeded 10 wt%, both the tensile strength and modulus of the PCL membranes increased. Additionally, the presence of RHC improved the hydrophilicity of membranes. Biologically, the addition of RHC, regardless of its concentration, significantly enhanced the adhesion, proliferation, and osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs). These effects were confirmed through various assays, including the CCK-8 assay, live/dead staining, as well as ALP and ARS staining. Further, real-time quantitative PCR and Western blot analysis revealed upregulation of osteogenesis-related genes and proteins. Transcriptome sequencing analysis suggested that the PI3K-Akt signaling pathway might play a critical role in the enhanced osteogenesis induced by RHC. Our results emphasize the potential of RHC/PCL nanofibrous membranes to advance the field of periodontal tissue repair.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Electrospinning; Periodontal regeneration; Recombinant collagen